FEATURES OF DISEASE IN BOYS WITH CONGENITAL MALFORMATIONS AND ACQUIRED DISORDERS OF GENITALS - I.V. Ivlieva; V.S. Polunin (Педиатрическая фармакология)
Control of growth, development and child health is carried out by district pediatricians and specialists of outpatient departments, the main principle in their work is to maintain the health of children and to support parents in the breeding of the child. A pediatrician should avoid deterioration of the existing pathology, carry out the rehabilitation of children of all ages, particularly in boys with congenital malformations and diseases of the genitals. Key words: health, children’s surgeon, malformations of genitals, varicocele, cryptorchidism, hypospadias, morbidity, boys. (Pediatric Pharmacology. — 2011; 8 (5): 102–105.)